Recasting West German elites : higher civil servants, business leaders, and physicians in Hesse between Nazism and democracy, 1945-1955 /: higher civil servants, business leaders, and physicians in Hesse between Nazism and democracy, 1945-1955. (2003) - Unknown
No abstract available